2021
DOI: 10.1007/s10900-021-00988-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SARS-CoV-2 Infection on Pregnancy Outcomes in an Inner-City Black Patient Population

Abstract: While data have shown that Black populations are disproportionately affected by COVID-19, few studies have evaluated birth outcomes in these understudied populations. This study hypothesized that SARS-CoV-2 infection would confer worse maternal and neonatal outcomes in a predominantly Black and underserved population in Brooklyn, New York City. In particular, SARS-CoV-2 is associated with higher rates of preterm birth, cesarean delivery, postpartum hemorrhage, lower APGAR scores, and neonatal resuscitation. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
(21 reference statements)
0
21
0
Order By: Relevance
“…Two thousand seven hundred ninety-five (2795) studies were identified through the search engines for the title and abstract reviews after removing 1254 duplicates. Out of the total screened abstracts, 120 were selected for full-text screening, of which 99 studies were excluded (mainly due to lack of a comparison group or the presentation of inadequate data), and 21 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] studies were included in this systematic review and meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two thousand seven hundred ninety-five (2795) studies were identified through the search engines for the title and abstract reviews after removing 1254 duplicates. Out of the total screened abstracts, 120 were selected for full-text screening, of which 99 studies were excluded (mainly due to lack of a comparison group or the presentation of inadequate data), and 21 [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] studies were included in this systematic review and meta-analysis ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were nine (42.9%) articles from single-center studies [ 14 , 15 , 16 , 17 , 20 , 21 , 22 , 25 , 27 ], eight (38.1%) from multicenter studies [ 18 , 19 , 23 , 24 , 26 , 29 , 31 , 32 ] and three (14.3%) from nationwide [ 28 , 30 , 34 ] studies. The remaining one (4.7%) was a multinational study [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This disagreement about reporting times is evident in the literature; many recent papers only report 5 mins Apgar scores, omitting 1 min scores without providing explanation for their absence ( 7 , 26 , 28 , 33 ). In keeping with the intended testing scheme, however, the vast majority of studies commonly report both 1 and 5 mins scores ( 2 , 24 , 27 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“… 21 In a cross-sectional study of diverse patients in New York tested for SARS-CoV-2, the odds of SARS-CoV-2 infection in patients whose preferred language was Spanish compared with those whose preferred language was English was 1.67 (95% confidence interval: 1.44-2.43). 12 While not analyzed separately, Liu et al 29 note that the top primary languages in their population of disproportionately infected minority patients were non-English languages including Haitian Creole, Spanish, Arabic, Bengali, Russian, French, and French Creole.…”
Section: Accessmentioning
confidence: 99%